Unusual cutaneous toxicity after prolonged use of Hydroxyurea in polycythemia vera: a case report - Elisa, Molinari; Gianfranco, Barabino; Eleonora, Arboscello; Lisette, Del Corso; Andrea, Bellodi; Vera, Sicbaldi; Serena, Favorini; Riccardo, Ghio; Enrico, Balleari (Journal of Hematology and Oncology Research, 2015)
Hydroxyurea (HU) is commonly used for the long-term treatment of patients with chronic myeloproliferative neoplasms. The drug is usually well tolerated in the large majority of subjects, although systemic and/or localized toxicities have seldom been reported. Here we report a case of unusual cutaneous toxicity due long-term use of HU in a patient with polycythemia vera.
Keywords: Hydroxyurea; Polycythemia vera; myeloproliferative neoplasms; mucocutaneous toxicity